Early Use of Small Bowel Follow Through Reduces Stay and Cost in Small Bowel Obstructions - Ali, Mohammad (Cureus, 2021)
Background According to the Nationwide Inpatient Sample in 2011, nearly 1,500,000 admissions with over 300,000 laparotomies were performed for adhesion-related small bowel obstructions (SBOs). Small bowel follow through (SBFT) consists of serial X-rays with oral Gastrografin contrast that can diagnose obstructions requiring operative intervention. Furthermore, the contrast has a therapeutic osmotic effect which may promote transit and resolve an SBO. The aim of the study was to determine if early SBFT administration to patients with SBO decreases length of stay (LOS), hospital costs, and can identify patients who will fail non-operative management (NOM). Methodology This is a single institution retrospective study conducted from 2010 to 2019 with a total of 476 patients. We divided patients into three groups: SBFT within <24 hours of admission (n = 40), SBFT >24 hours after admission (n = 198), and did not receive SBFT (n = 238). We compared the overall LOS, hospital costs, and time from SBFT to the operating room using an analysis of variance. Results LOS significantly differed between groups with SBFT within ≤24 hours having an average LOS of 6.95 days compared to 10.65 days in the SBFT after >24 hours and 11.75 days in the no SBFT group (p = 0.005). Median time to the operating room in patients receiving SBFT was one day, which was significantly shorter than a median time of four days for no SBFT group (p = <0.05). Decreased LOS by 4.8 days equated to saving $8,657 per patient. Conclusions SBFT administered within 24 hours decreases LOS, overall costs, and time to operating room in patients who fail NOM.